1978
DOI: 10.1080/00288233.1978.10427404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fertiliser nitrogen on nitrogen fractions and nonstructural carbohydrates in grazed grass-clover herbage

Abstract: Contents of Nand nonstructural carbohydrate fractions were measured over a year in herbage from a grazed ryegrass-white clover pasture, which had been fertilised with limeammonium nitrate at an annual rate of 0 (No), 112 (N112), and 448 (N448) kg N/ha. Total N wntent of the mixed herbage was often greater than 4% dry weight, and was highest in earlY spring and lowest in late summer. Levels in many cuts were increased significantly by the N448 treatment; the N112 treatment had little effect. The non-protein N a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1978
1978
1990
1990

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…A comparable value for a grass-clover pasture not receiving fertiliser nitrogen in southern England is 295 kg N /ha (Whitehead 1970). Herbage nitrogen contents and nitrogen fractions are considered in detail by Ross et al (1978).…”
Section: Herbage Nitrogen Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…A comparable value for a grass-clover pasture not receiving fertiliser nitrogen in southern England is 295 kg N /ha (Whitehead 1970). Herbage nitrogen contents and nitrogen fractions are considered in detail by Ross et al (1978).…”
Section: Herbage Nitrogen Yieldsmentioning
confidence: 99%
“…In order to better quantify this response of pasture to nitrogen, the effects of varying inputs of fertiliser nitrogen on the performance of a grazed ryegrass-white clover pasture were studied. At the same time, the influence of applied nitrogen on some chemical characteristics of the mixed herbage was measured and is described by Molloy et al (1978) and Ross et al (1978) .…”
Section: Introductionmentioning
confidence: 99%
“…In terms of growth rate of above-ground herbage, the mean daily increase was 12 lr.g DM/ha. The peak value of 33% Ball et al (1978) and Ross et al (1978) reported the much lower value of 16% soluble carbohydrate. Temperatures were lower in the present study (July and August min.…”
Section: Resultsmentioning
confidence: 99%
“…Both studies showed that the soluble carbohydrate was comprised largely of simple sugars. In the North Island of New Zealand much lower values of soluble carbohydrate (about 4-17% of DM) have been reported for perennial ryegrass (Johns 1955;Ross et al 1978). These values would be for leafy herbage and would not include much ofthe basal tissues ofthe grass where soluble carbohydrate is "stored".…”
Section: Introductionmentioning
confidence: 99%
“…C extracted in hot water was obtained by heating plant material (0.100 g) with 15.0 mL water in a stoppered tube, with occasional shaking, in a water bath at 100°C for 2 h. The mixture was filtered while hot, and soluble-C determined as above. Both fractions would probably have contained appreciable amounts of nonstructural carbohydrates, including starch in the hot water extract (Ross et al, 1978). Mineralization of C and N was determined in biometer flasks by mixing plant material, harvested from each of the S o and $20 plots, with field-moist S o or $20 soil (equivalent to 20.0g at 60% of WHC); the amounts of plant material added were equivalent to 1% of the oven-dry weight of soil.…”
Section: Plant Properties and C And N Mineralizationmentioning
confidence: 99%